Validating an alternate version of the chewing function questionnaire in partially dentate patients - Aridome Kumiko; Inukai Mika; John Mike T; Baba Kazuyoshi; Igarahsi Yoshimasa (BMC, 2009)
Abstract Background The aim of this study was to investigate the dimensionality, reliability, and validity of an alternate version of the chewing function questionnaire in partially dentate patients in Japan. Methods Subjects were partially dentate patients who attended the prosthodontic clinic at Tokyo Medical and Dental University (N = 491, 71% women, mean age (± SD): 63.0 ± 11.5 years). The questionnaire asked each subject to rate his or her ability to chew 20 common Japanese foods. For each individual, responses were combined to yield a chewing function summary score, with higher scores indicating better self-reported chewing ability. We used exploratory factor analysis to investigate the scores' dimensionality. For validity assessment, we computed the correlations between the chewing function score and oral health-related quality of life (OHRQoL, as measured by the Japanese 14-item Oral Health Impact Profile (OHIP-14)) Internal consistency of scores and test-retest reliability were investigated by asking a subset of subjects (N = 62) to complete the questionnaire twice, 2 weeks apart. Results Exploratory factor analysis provided some evidence that self-reported chewing ability can be characterized by a summary score as the original authors suggest. Support for the validity of chewing function scores using the alternate version of the questionnaire was derived from correlations with OHIP-14 scores (r = -0.46, 95% confidence interval (CI): -0.53 to -0.39); thus, better chewing ability was associated with less impaired OHRQoL. Internal consistency was 'satisfactory,' with a Cronbach's alpha of 0.90 (lower limit of 95% CI: 0.89). The test-retest reliability was 'good,' with an intraclass correlation coefficient of 0.69 (95% CI: 0.56 to 0.82). Conclusion The alternate version of the chewing function questionnaire can be used as a stand-alone instrument because of the demonstrated reliability and validity of scores obtained using the questionnaire in partially dentate patients.